Pengaruh Kepatuhan Minum Obat dan Efek Samping Obat Terhadap Keberhasilan Terapi pada Pasien Tuberkulosis Paru di Poli TB Dots RSUD Undata Provinsi Sulawesi Tengah: Penelitian - Andi Riansyah; Siti Yartin; Sugiyarso Sanan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Pulmonary tuberculosis remains a major global health problem that requires long-term treatment and a high level of medication adherence. This study aimed to analyze the effect of medication adherence and drug side effects on treatment success among pulmonary tuberculosis patients at the TB DOTS Clinic of Undata General Hospital, Central Sulawesi Province. Methods: This research employed a quantitative approach with a causal-comparative design. A total of 33 respondents were selected using purposive sampling. Results: The findings revealed that most respondents demonstrated a high level of adherence, experienced moderate side effects, and achieved successful treatment outcomes. The Spearman rank test showed a significant relationship between medication adherence and treatment success p = 0.001 (p < 0.05), as well as between drug side effects and treatment success p = 0.021 (p < 0.05). Conclusion: Medication adherence and drug side effects significantly influence treatment success among pulmonary tuberculosis patients at the TB DOTS Clinic of Undata General Hospital, Central Sulawesi Province. Recommendation: It is suggested that public awareness be strengthened regarding the importance of medication adherence as a key factor in achieving successful pulmonary tuberculosis treatment.